First report of Cryptosporiopsis tarraconensis causing leaf lesion of Corylus avellana in Central Europe (Poland) - Katarzyna Patejuk; Anna Baturo-Cieśniewska; Agata Kaczmarek-Pieńczewska; Amelia Piegdoń; Wiesław Fałtynowicz; Pola Wasilewska; Magdalena Ogonowska (Annals of Forest Science, 2024)
Abstract Key message As a result of our research, we determined that Cryptosporiopsis tarraconensis—as a new species for Central Europe—is the causative agent of leaf lesions in natural populations of hazel (Corylus avellana). Until now, this species had not been described in a natural population of C. avellana or out of the temperate climate. This is the fifth notification of this rare fungus in the world and the first from Central Europe and the natural population of the host.